STEM Highlights: Principles, Frameworks and Implementation Strategies in Improving Scientific Literacy - Yuliardi, Ricki; Dahlan, Jarnawi A. (International Journal on Emerging Mathematics Education, 2022)
The 21st-century era, marked by the rapid development of information technology, requires students to be adaptive and have several skills that must be mastered to be able to compete in today's era. The important skills in the 21st century or so-called The 4C-skills consist of communication, collaboration, critical thinking, in general containing specific skills that need to be empowered in learning activities, such as problem-solving skills, critical thinking, communication skills, collaborating, innovation and creation, literacy, information metacognition, and various other skills. However, the reality in the field is based on the results of TIMSS and PISA, where this test measures the mathematics, science, and literacy skills of developed and developing countries, Indonesia's ranking is still in the lowest rank. The method used in this research is the literature study method, which examines the STEM principles, implementation strategies, and their prospects for improving scientific literacy skills. Based on the results, the success key while implementing STEM in the classroom is to prepare STEM educators with a conceptual understanding of the principles, frameworks, and strategies of integrated STEM implementation and learning theories from the four STEM fields. It should be integrated to increase the pedagogical skills and to mastery the technology as a learning support. Also, the development of professional experience for teachers in implementing STEM in various cross-materials is needed to provide a strong conceptual framework of an integrated STEM approach and build their confidence in teaching an integrated STEM approach. Hopefully, this article can provide a comprehensive overview of improving scientific literacy as one of the keys to improving the quality of quality education in Indonesia.